Neither motility nor chemotaxis plays a role in the ability of Escherichia coli F-18 to colonize the streptomycin-treated mouse large intestine. - McCormick, B A (1990)
Escherichia coli F-18, isolated from the feces of a healthy human in 1977, is an excellent colonizer of the streptomycin-treated mouse large intestine and displays normal motility and chemotaxis ability. A chemotaxis-defective derivative of E. coli F-18, E, coli F-18 CheA-, and a nonflagellated derivative, E. coli F-18 Fla-, were constructed. These strains were found to colonize the streptomycin-treated mouse large intestine as well as E. coli F-18 when mice were fed both E. coli F-18 and either the CheA- or Fla- derivative at high levels (10(10) CFU of each strain per mouse) or low levels (10(4) CFU of each strain per mouse). Furthermore, E. coli F-18 lost motility and chemotaxis ability when grown in colonic or cecal mucus in vitro despite retaining the ability to synthesize flagella. Thus, it appears that neither motility nor chemotaxis plays a role in the ability of E. coli F-18 to colonize because this strain becomes functionally nonmotile upon growth in the streptomycin-treated mouse large intestine.